Unusual visual loss after snakebite - Tungpakorn,N (2010)
Snakebites are endemic in some parts of Thailand, being associated with several complications. Ocular disturbances are uncommon, except in cases of corneal or conjunctival injury, when the eye is directly exposed to the snake venom. The present study presents a case of combined ophthalmic artery occlusion and transient central retinal artery occlusion with macular ischemia after a Russell's viper bite.